Parenting adolescents: Parent-Teen communication training - Efi Fitriana; Syipa Husni Fadillah; Fitri Ariyanti Abidin (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2023)
Puberty is often experienced by adolescents in relation to psychological changes, including letting go of dependence on parents to achieve greater independence. Adolescents begin to spend more time with their friends, and share less information with their parents. However, support and direction from parents are still needed by adolescents, considering that they will grow into adults with all the complexity of their problems. So parents need to understand the changes that adolescents are experiencing, and how to assist adolescents in dealing with these changes. "Parenting Adolescents: Parent-Teen Communication Training" is aimed to increase parents' understanding of the characteristics of adolescent development and how to communicate with adolescents. The training was conducted through three stages, preparation, implementation, and follow-up. There were 38 parents who have children aged 12-23 years attended training. The training was held face-to-face on Saturday, July 29, 2023, at Madrasah Thosin Cikopo, Cipacing Village, Jatinangor District. "Parenting Adolescents: Parent-Teen Communication Training" was considered fun and useful by parents who have teenage children. The parents were satisfied with the material provided, which was in accordance with their needs.